Gastric outlet obstruction by polypoid tumors - Cerwenka, Herwig (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Cerwenka H. Gastric outlet obstruction by polypoid tumors. Turk J Gastroenterol 2018; 29: 243-4.